Pelatihan dan Pendampingan Kader Kesehatan Lansia di wilayah Kerja Puskesmas Gladakpakem untuk Meningkatkan Kesehatan Gigi dan Mulut - Dewi Kristiana; Amiyatun Naini; Ady Soesetijo; Rahardyan Parnaadji; Achmad Gunadi; Afif Surya Adena; Ardhianing Hardita (Fakultas Kedokteran Gigi, Universitas Jember, 2024)
In order to achieve dental and oral health indicators, promotive and preventive efforts are needed in addition to curative and rehabilitative measures. Promotive action is by conducting training for elderly cadres about dental and oral health for the elderly and counseling about dental and oral health for the elderly. The dental and oral health status of the elderly in the working area of the Gladapakem Health Center has received little attention. As well as the knowledge and attitude of the elderly towards dental and oral health is also low; it can be seen that many older adults with no teeth are left without wearing dentures. Elderly cadres at Posyandu have a significant role. Based on interviews with nurses holding the elderly Posyandu program in the working area of the Gladakpakem Health Center, Sumbersari District, Jember Regency, the activities carried out so far are checking blood pressure, body weight, if there are complaints referred to the Health Center. Meanwhile, dental and oral examination activities and counseling on dental and oral health carried out by health cadres are rarely done. Knowledge of dental and oral health cadres also needs to be improved. So the servant carried out the service by holding training and mentoring for elderly health cadres in Posyandu Catleya Kebonsari Village and Kranjingan Village regarding dental and oral health. From the results of community service activities, it can be concluded that there is an increase in skill knowledge about elderly dental and oral health in elderly cadres.Keywords: dental and oral health, elderly patient, posyandu.